(untitled) (MAUSAM, 2021)
The present study has been focused to recognize and quantify the drought condition in Bihar Agro-climatic Zone-III, which falls in the drought-prone region of Bihar. The zone covers the whole South Bihar region, comprising of seventeen districts. The drought severity assessment in the study area has been carried out by two methods i.e., the rainfall departure analysis and the probability analysis. The research work has been carried out at a grid level consisting of fifty-five grids. The analysis of work has been further evaluated district-wise and in addition the result has been interpreted for the two agro-climatic zones zone-iii (a) and zone-iii (b). For decades, the area is under the influence of frequent droughts due to uneven distribution of rainfall. The grid forty-seven of Bhagalpur district having maximum drought frequency of once in 1.87 years and also faces a maximum number of sixty-two drought years in the period of 116 years, as resulted from rainfall departure method. The maximum annual rainfall departure of -82.99% was observed for the grid-32 (G-32) of Banka district, during the year 1978-79, with a return period of once in 2.7 years. The probability analysis concludes that the areas influenced by grids 37,42,45, and 47 are drought-prone (probability of 75% mean rainfall being less than 80%). The departure as well as the probability analysis indicates that the grid-47 as drought-prone. This shows the compatibility of the two methods in meteorological drought assessment in general and particularly the most drought severe condition of the grid-47.